Representasi Realitas Sosial Islami dalam Fotografi Dokumenter di Media Digital - Oland, Muhammad Askolani; Murofiq , Akhlis (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
Documentary photography is one form of visual media that has the power to represent social reality in depth. The development of digital media, especially Instagram, has expanded the reach of documentary photography to a broader and more diverse public. This research aims to analyze how social reality is represented through visual content on the Instagram account @natgeoindonesia. By using qualitative content analysis methods on ten selected photos, this research examines visual elements such as subjects, symbols, colors, and narratives in each post. The results show that @natgeoindonesia not only showcases the beauty of nature and culture in Indonesia but also incorporates strong social and humanitarian messages through symbolic visual imagery. These findings affirm that documentary photography in digital media serves as a means of social communication that can shape public opinion and collective awareness.